2000
DOI: 10.1001/archinte.160.7.967
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Anticoagulation Management Among Patients With Atrial Fibrillation

Abstract: We found significant deficiencies in the practice of warfarin management and suggestive evidence that anticoagulation services can partially ameliorate these deficiencies. More research is needed to describe the quality of anticoagulation management in typical practice and how this management can be improved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
168
3
21

Year Published

2000
2000
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 274 publications
(208 citation statements)
references
References 15 publications
16
168
3
21
Order By: Relevance
“…Remiantis atliktomis studijomis, nustatyta, kad tik apie 50 proc. gydymo atvejų pavyksta pasiekti bei išlaikyti krešumo rodiklių reikšmes rekomenduojamose ribose [9,18,19]. Nepakankamą krešumo kontrolę bei nevienodą atsaką į varfariną gali lemti keletas veiksnių: gydymo režimo laikymasis, paciento amžius, kūno masė, genetinis polinkis, varfarino sąveika su kitais medikamentais ar maisto produktais, šalutinės ligos bei jų paūmėjimai ir atstumas nuo gydymo įstaigos [18, [20][21][22].…”
Section: įVadasunclassified
“…Remiantis atliktomis studijomis, nustatyta, kad tik apie 50 proc. gydymo atvejų pavyksta pasiekti bei išlaikyti krešumo rodiklių reikšmes rekomenduojamose ribose [9,18,19]. Nepakankamą krešumo kontrolę bei nevienodą atsaką į varfariną gali lemti keletas veiksnių: gydymo režimo laikymasis, paciento amžius, kūno masė, genetinis polinkis, varfarino sąveika su kitais medikamentais ar maisto produktais, šalutinės ligos bei jų paūmėjimai ir atstumas nuo gydymo įstaigos [18, [20][21][22].…”
Section: įVadasunclassified
“…Наличие МА увеличивает риск инсульта в 5 раз [3]. Риск инсульта у пациентов с ФП одинаков вне зависимо-сти от ее формы [4]. Больные даже с короткими пароксизмами ФП имеют высокий риск тромбоэмбо-лических осложнений, существенно не отличаю-щийся от риска у больных с постоянной формой МА.…”
Section: применение новых оральных антикоагулянтов для профилактики тunclassified
“…Даже в рамках клинических исследований, пациенты находились в целевых уровнях МНО в среднем около 50% времени. Этот показатель колебался от 36% до 63% в различных исследованиях и сильно отличался в разных странах, достигая 80% [4,[7][8][9][10][11][12]. Таким образом, процент времени нахождения в терапевтическом диапазоне является одним из наи-более значительных показателей эффективности терапии варфарином.…”
Section: применение новых оральных антикоагулянтов для профилактики тunclassified
See 1 more Smart Citation
“…[4][5][6][7][8][9][10][11] Two studies have shown that more than 50% of patients without contraindications to anticoagulation therapy are receiving warfarin, but other studies have documented substantially fewer patients receiving treatment consistent with guidelines. [12][13][14][15][16][17][18][19][20] The challenge is to identify those patients for whom the benefit from treatment outweighs the risk. Patient-specific characteristics known at the time of decision making substantially alter the patient's risk of both ischemic stroke and hemorrhage with anticoagulation.…”
Section: Introductionmentioning
confidence: 99%